A methodical study of the role of trust at various development stages of virtual organisations. (1st January 2014) - Yasir, Muhammad; Majid, Abdul; Johnson, Phil
Virtual organisation (VO) is an outcome of technological advancements and the introduction of structural flexibilities in organisations. It is a temporary combination of internally independent parties to exploit the emerging market opportunities. The need to demonstrate extra efficiency in its limited life-span, geographical distribution of parties, lack of face-to-face communication, and the absence of complete information about partners working at a distance call for establishing trust-based relationship in virtual organisations. Almost all the researchers agree upon the importance of trust for virtual organisation but its nature and role at various development stages of these organisations is still unexplored. Therefore, in this research we have conducted a methodical investigation to propose the models explaining nature and role of trust at various development stages of virtual organisations. The result of this research would help the members to formulate effective trust-based relationship that could ultimately increase the efficiency and performance of virtual organisations.